Presenting a Model for Managing the Development of Sound Ethics in Shahed Schools of Shahr-e Kord County Inspired by Grounded Theory - Eskandari Asl, Heshmatullah; Dolatyari, Forouzan; Alipour, Hamed (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of this research was to present a model aimed at enhancing the education of sound ethics in the Shahed schools of Shahr-e Kord County. Methods and Materials: The present research utilized a sequential exploratory mixed-method design. The statistical population in the first part of the research (qualitative) consisted of 20 education experts from the city of Shahr-e Kord, selected through purposive sampling based on the principle of data saturation. In the quantitative section, 300 students from the second secondary grade in Shahr-e Kord were selected as the sample using multi-stage cluster sampling and the Cochran formula. Data collection tools in the qualitative section included semi-structured interviews. In the quantitative section, a researcher-made questionnaire was used, with its face validity assessed through a pilot study, content validity evaluated by expert judgment, and construct validity examined through factor analysis. Additionally, the reliability of the questionnaire was calculated using Cronbach's alpha coefficient and the test-retest method. Data analysis in the qualitative section was conducted through content analysis, and in the quantitative section, exploratory and confirmatory factor analysis and one-sample t-tests were performed using SPSS-V22 and LISREL-V8 software. Findings: The results indicated that sound ethics comprise four dimensions: educational, social, environmental, and religious. The components of the educational dimension include teacher, curriculum, classroom environment, and school management. The social dimension encompasses group values, empathy, social trust, and mutual respect. The environmental dimension includes the moral atmosphere, encouragement and punishment, parents' literacy and income level, and an individual's socioeconomic status. The religious dimension involves adherence to religious values, religious beliefs, and chastity. Conclusion: The research findings demonstrated that the model presented in this study for the development of sound ethics in the schools of Shahr-e Kord County has a desirable fit.